PERANAN SATUAN POLISI PAMONG PRAJA MENEGAKKAN PERATURAN WALIKOTA JAMBI NOMOR 21 TAHUN 2020 - Satriadi Satriadi; Ansorullah Ansorullah; Muhammad Eriton (Limbago: Journal of Constitutional Law, 2022)
Abstract The purpose of this research was to: 1) knowed the role of the Jambi City civil service police unit to enforcing mayor’s regulation number 21 of 2020 dan 2) knowed the obstacles faced by of the Jambi City civil service police unit to enforcingmayor’s regulation number 21 of 2020. This research was juridical empirical with descriptive data analysis. The result of this study was: 1) the role of the Jambi City civil service police unit to enforcingmayor’s regulation number 21 of 2020 consists of three forms, namely supervision is carried out by conducting raids and patrils in coordination with the Satgas Covid-19, TNI/Polri and ormas, the role of coaching is carried out by providing direct appeals and through posters, brochures and billboards, as well as the role of controlling by applying strict sanctions for business locations that violate. 2) The obstacles faced by of the Jambi City civil service police unit to enforcingmayor’s regulation number 21 of 2020 was lack of public awareness and lack of business owner awareness.